Teachers’ Language Awareness in Indonesian EFL Context: A Systematic Literature Review - Risdaneva (Jurnal Pengembangan Profesi Guru dan Dosen, 2025)
This systematic literature review explores studies on teacher language awareness (TLA) within the Indonesian English as a Foreign Language (EFL) context. TLA is defined as the knowledge and metacognitive awareness that language teachers have of language, language use, and language teaching and learning. The reviewed literature consists of peer-reviewed articles and conference proceedings that were extracted from databases such as Google Scholar, JSTOR, ERIC, and SAGE Journals. The review synthesises empirical research on TLA, and closely related constructs such as language awareness, teacher awareness, multilingual beliefs in Indonesia, identifies gaps, and provides recommendations for teacher education and further research. Key findings reveal the key dimensions of TLA research In Indonesian EFL context, several mediating factors of TLA development, and several gaps in the literature as well as future directions of TLA research in Indonesia. These findings suggest that teacher language awareness notion is increasingly recognised and Indonesian EFL teachers exhibit growing awareness of their language practices. Implications for in-service professional development, pre-service teacher training, and policy are discussed. These recommendations are aimed at fostering more profound language awareness in Indonesian EFL teaching